Comparison of Different Techniques for the Diagnosis of Trichomonas Vaginalis Infection in Females at Reproductive Age - Muntaha A. H. Nasir, Al-Idreesi S.R, Wasfi A. Al-Masoudi, (Pakistan Journal of Medical & Health Sciences, 2022)
Trichomoniasis is a sexual transmitted disease that affects human fertility, abortion, low birth weight, in women, caused by the protozoan parasite Trichomonas vaginalis. The aim of the study was to determine the efficacy of different techniques for diagnosing of trichomoniasis in women. A case control study was carried out 230 women their age from (20-60 years) that divided into two groups (155 as patient groups and 75 as control groups without any symptoms of infection) through the period between November 2020 and July 2021 in Basra Maternity Hospital.The detection rate of T. vaginalis infection was 10 (38.5%), 17 (65.4%), 18 (69.2%), 21 (80.8%) and 25 (96.2%) using wet mount, Giemsa stain, AO, culture and in pouch system, respectively. The infection indicates that the highest frequency of positive samples 10 (13.2 %), 18(14.2%) ,21(15.8%) in young women aged 20-30 years, in rural areas and in women with primary education, respectively. The highest rate of infection with T. vaginalis was detected by in pouch system in this study offers a useful rapid screening tool and provides an excellent alternative for definitive laboratory diagnosis of T. vaginalis, thus reducing spread and transmission of the infection as well as minimizing the complication sequels. Keywords: Trichomonas vaginalis, Acridine orange, Diamond modified culture, in pouch TV.